Investigation of second grade viscoelastic non-Newtonian nanofluid flow on the curve stretching surface in presence of MHD - Kh. Hosseinzadeh; M.R. Mardani; M. Paikar; A. Hasibi; T. Tavangar; M. Nimafar; D.D. Ganji; Mohammad Behshad Shafii (Results in Engineering, 2023)
MHD extended flow of second-grade viscoelastic nanofluid is studied in two-dimensional mode on a curve stretching surface. Items like Joule heating and curvature parameter have been applied to inspect the heat transfer and mass transfer rates. To produce the nonlinear ordinary differential system, appropriate transformations are used. The quasi-linearization method is utilized to derive the solutions numerically. The impact of specific variables on the properties of fluid has been studied. Conclusions indicate that the increase in Schmidt number halted the fluid concentration, whereas temperature grew because of an increment in radiation parameter. Viscous fluid velocity and concentration are reduced faster in comparison to viscoelastic fluid. The surface drag force is an increasing function of the non-Newtonian fluid. When values of Nt and Nb are increased, the heat transfer rate of second-grade fluid increases compared to Newtonian fluid. Schmidt number and chemical reaction parameters highly affect the mass transfer of second-grade fluid compared to Newtonian fluid.